1977
DOI: 10.1038/bjc.1977.60
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of tumour cells modified with various chemicals

Abstract: Summary.-Mouse tumour cells were treated with various chemical modifiers. The number of modifying groups per cell was determined with labelled reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Multiple injections of inactivated cells are required to elicit a protective response with weakly antigenic tumors [15,16,30]. Systematic studies therefore were carried out to determine the optimum dose-regimens for immunizing mice to X-irradiated cells of the IP line of WEHI tumor cells.…”
Section: Lmmunogenicity Of X-irradiated Cells Given In Various Dose Rmentioning
confidence: 99%
“…Multiple injections of inactivated cells are required to elicit a protective response with weakly antigenic tumors [15,16,30]. Systematic studies therefore were carried out to determine the optimum dose-regimens for immunizing mice to X-irradiated cells of the IP line of WEHI tumor cells.…”
Section: Lmmunogenicity Of X-irradiated Cells Given In Various Dose Rmentioning
confidence: 99%
“…THE ATTENUATION of tumour cells by chemical treatment before using them as immunogens has been considered attractive from several viewpoints (Prager & Baechtel, 1973;Sanderson & Frost, 1974;Staab & Anderer, 1977), particularly since previous studies have indicated that immunization with chemically modified antigens, such as flagellin, results in enhanced cell-mediated immunity and depressed antibody responses (e.g. Parish & Liew, 1972).…”
mentioning
confidence: 99%